Optimization of Financial Management at Idhotun Nasyi’in Islamic Boarding School using a Website Application - Arinil Haqqoh; Kemal Farouq Mauladi; M. Hasan Wahyudi (Journal of Artificial Intelligence and Engineering Applications (JAIEA), 2026)
Idhotun Nasyi'in Islamic Boarding School faces challenges in financial management due to its manual reliance on Microsoft Excel, which is prone to data loss, input errors, and tracking difficulties. This research aims to design and build a web-based financial management application to address these issues. Developed using the System Development Life Cycle (SDLC) waterfall model with PHP and MySQL, the application features core functionalities such as income and expense management, transaction categorization, and real-time financial report generation in PDF format. Black box testing results indicate that the application functions effectively, simplifying the tasks of administrators and treasurers in monitoring cash flow. The implementation of this system is expected to enhance the accuracy, efficiency, and transparency of the boarding school's financial management.